Inclusion of Peak Expiratory Flow for Selection of the 'Best' Forced Vital Capacity Manoeuvre - Francesco Di Pede; Francesco Pistelli; Giovanni Viegi; Paolo Paoletti; Alessandro Celi; Laura Carrozzi; Mariella Vellutini; Giuseppe Pistelli; Carlo Giuntini (Canadian Respiratory Journal)
OBJECTIVE: To assess four different criteria for selecting the 'best' forced vital capacity (FVC) manoeuvre to be used for clinical diagnostic purposes.